Analysis of SO2, NOx, CO and PM2,5 Pollutant Dispersion from The Combustion of Domestic Waste Incinerators - Vanya Nurulita Santana; Didin Agustian Permadi (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The population of Bandung City in 2024 reached 2,579,837 people with a total daily waste generation of 546,151.49 tons/year. The largest composition of waste is domestic waste (household waste). The high volume of waste puts serious pressure on the Final Processing Site (TPA). As a form of commitment to achieving national waste management targets, the Bandung City government continues to encourage the implementation of the Reduce, Reuse, and Recycle (3R) approach. One solution from the implementation of 3R is the incineration of residual waste using a waste incinerator. However, the composition of waste greatly affects the quality of emissions produced. The content of organic materials, plastics, heavy metals, and water content in the waste can produce hazardous pollutants such as particulates, carbon monoxide (CO), nitrogen oxides (NOx), dioxins, and furans if the incineration process is not carried out optimally. Air quality monitoring in the surrounding area needs to be considered, given that the effluent from waste incineration in incinerators is dispersed into the ambient air using AERMOD software.